(untitled) (Slavic Studies, 2025)
The starting premises of the research are related to some of the current tendencies in contemporary literature that articulate the interdiscursive relations between literature and theory, which results in the creation of genre hybrids such as theoretical fiction. The theoretical premises of the research relate to the elaborations on theoretical fiction by Mark Currie, which will be interpretively applied to the novel The Symmetry Teacher by the Russian author Andrei Bitov.